Power converters with digital filter feedback control - Wu, Keng C., 1948- (Academic Press, an imprint of Elsevier, 2016)
Power Converter with Digital Filter Feedback Control presents a logical sequence that leads to the identification, extraction, formulation, conversion, and implementation for the control function needed in electrical power equipment systems. This book builds a bridge for moving a power converter with conventional analog feedback to one with modern digital filter control and enlists the state space averaging technique to identify the core control function in analytical, close form in s-domain (Laplace). It is a useful reference for all professionals and electrical engineers engaged in electrical power equipment/systems design, integration, and management.